BOOK REVIEW: Lucian Boia, “De la Dacia Antică la Marea Unire, de la Maria Unire la România de azi”, Bucureşti: Humanitas, 2018 - SAS, Florina (Studia Universitatis Babeș-Bolyai Historia, 2019)
As many people know, 2018 was the year that brought in front of us a lot of historical publications dedicated to the Centenary of the Great Union ofthe Romanians. Some of the written books present the events that happened during the First World War and after it. Others purpose was to expose some new opinions upon these facts, while the last but not the least is the category of books which intend to destroy the myths created about this important moment in the history of the Romanians. This third category also includes the book written by Lucian Boia, entitled De la Dacia Antică la Marea Unire, de la Maria Unire la România de azi (From the Ancient Dacia to the Great Union, from the Great Union to today’s Romania), published in 2018, at Humanitas Publishing House. It contains only one hundred pages, being more like an essay which exposes the author’s discontent with the instrumentalization of the entire Romanian history, in order to serve for the moment of the Great Union. In the short foreword, Boia shows his disagreement with the anachronisms existing in historigraphy and with the attempt of the Romanian historians to unify the distant past of the Romanian territories.The book is structured in seventeen short chapters, bringing in our attention the main problems of the Romanian historiography; among it’s pages, Boia mentions and even criticizes some of the greatest Romanian historians, such as Neagu Djuvara, Vasile Pârvan, or Ioan Bogdan. Even if, when reading the title, the book seems to be one dedicated to a very short presentation of the true Romanian past, devoid of myths, in reality, it’s chapters are more like a harsh criticism of historiography and above the myths which are deforming the real history. Boia’s pleading begins with a discussion about the ancient Dacia. He considers the idea of continuity between Dacia and Romania like a dacian trap, where Pârvan or Densuşianu fell. The author considers that these historians made mistakes when they emphasized, in some cases, the exclusive dacic origins of the Romanians. In the end of the first chapter, Boia says that the unification of the territories inhabited by a majority of Romanians happenend due to the natural right, not to the historical right which researchers are trying to accentuate.